Territorial context and school organization: French rural school, from idealization to stigmatization - Alpe, Yves (Swiss Journal of Educational Research, 2012)
The education system in rural areas has always had problems. These have been aggravated recently by the socio-economic climate. The function of rural schools as a place for pupils to socialise is widely acknowledged, and celebrated. In contrast, the academic performance of rural schools students is often reputed to be inferior to that of their urban counterparts – an assumption that has been the subject matter of numerous studies. These studies question whether the stigmatisation of rural areas affects the attitude of classroom staff towards pupils, and the part played by differences in territorial education policies in creating disparages in academic performance, as shown in the French study.